Synopsis, Agricultural mechanization in Ethiopia: Evidence from the 2015 Feed the Future survey - Berhane, Guush; Hirvonen, Kalle; Minten, Bart (International Food Policy Research Institute, 2016)
In this research note, we provide a preview of results from a study of agricultural mechanization in Ethiopia. Our research shows that 9 percent of farmers in the Feed the Future regions of Ethiopia used mechanization at some point during the agricultural year 2014/15. We find that mechanized ploughing was most widespread (5 percent), while mechanized threshing and harvesting was reported by 3 and 2 percent of households, respectively. We further examine the uptake of different forms of mechanization through a number of associations. The results show that farm size and rural wages are positively associated with the adoption of mechanization, while remoteness is negatively linked. These findings suggest that as Ethiopia’s economy transforms and leads to higher rural wages, as well as with further development of its infrastructure, more demand for mechanized agricultural services will likely arise. Having policies that actively assure widespread availability of appropriate mechanized services at low cost, seem likely to benefit Ethiopia’s agricultural transformation.